PELATIHAN BAHASA INGGRIS UNTUK PEMANDU WISATA KELOMPOK SADAR WISATA (POKDARWIS) DI DESA WISATA JAGALAN YOGYAKARTA - Wibowo, Hermenegildus Agus; Marita Nurharjanti,; Rosyidah Jayanti Vijaya, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The purpose of organizing English training for tour guides in Jagalan Tourism Village, Yogyakarta is to improve the English language skills of Pokdarwis tourism partners so that they can provide services to foreign tourists well which will directly support the progress of the tourism village. In this activity, the stages of service activities begin from proposing and identifying problems, preparation, socialization, implementation of activities and the implementation and evaluation of activities. In the implementation of this training, English practice and learning methods are applied. The training methods provided are interactive games, speaking, listening, writing and roleplay aimed at improving the participants' English skills. Interactive games provide participants with the opportunity to learn English in a fun way which is expected to have a positive impact on participants' desire and motivation to remain consistent in learning English. Training with the simultaneous application of speaking, listening, and writing skills could develop the trainees' English skills efficiently. These language skills are needed for professionals such as tour guides. Weaknesses or limitations in the vocabulary of the trainees can be targeted by researchers and community service teams to develop a more specific approach to improving English vocabulary mastery. This approach will benefit the English language skills of the tour guide in Jagalan Tourism Village